PENGARUH SIKAP WAJIB PAJAK MENGENAI FUNGSI PAJAK, PERSEPSI WAJIB PAJAK DALAM PELAKSANAAN SANKSI DENDA, PELAYANAN FISKUS, DAN SPPT TERHADAP KEBERHASILAN PENERIMAAN PBB KOTA PEKANBARU - Rizka Wahyuni Siregar; Hardi Hardi; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the effect caused by the variable The Attitudes regarding the Tax Function, Perception of Tax payers on The Implementation of Financial Penalties, The Service Tax Authorities, and SPPT With PBB Income success. This study uses convenience sampling with 100 samples obtained from the calculation formula slovin. The data collection techniques in this study is in the form of questionnaires, while data analysis technique used is multiple regression analysis were processed with SPSS version 17 for Windows. From the results of the testing that has been done, simultaneous regression test (F test) showed that all independent variables studied have a simultaneous effect on the variable PBB Income success. Partial regression test (t test) showed that all independent variables studied partial effect on the variable The land and Building Tax Income success. The magnitude of the effect caused by Adjusted R2 by four variables together against the dependent variable 65,4%, while the remaining 34,6% is influenced by other variables not examined in this study.Keywords: Taxpayer Attitudes, Perception Tax payers, Service Tax, and SPPT